Patience, Cognitive Abilities, and Cognitive Effort: Survey and Experimental Evidence from a Developing Country - Stefania Bortolotti; Thomas Dohmen; Hartmut Lehmann; Frauke Meyer; Norberto Pignatti; Karine Torosyan (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
We shed new light on the relationship between cognition and patience, by providing documenting that the correlation between cognitive abilities and delay discounting is weaker for the same group of individuals if choices are incentivized. We conjecture that the exertion of higher cognitive effort, which induces higher involvement of the cognitive system, moderates the relationship between patience and cognition. To test this hypothesis, we analyze the relationship between various measures of cognitive ability, including the cognitive reffection test (CRT), a symbol-correspondence test, a numeracy test, as well as self-reported math ability and the interviewer's assessment of the respondent's sharpness and understanding, and different measures of patience, including incentivized choices between smaller sooner and larger later monetary payments and hypothetical inter-temporal trade-offs, for 107 subjects drawn from the adult population in Tbilisi (Georgia).
Keywords: 330